Characterization of a Y-Family DNA Polymerase eta from the Eukaryotic Thermophile Alvinella pompejana. (15th July 2010) - Kashiwagi, Sayo; Kuraoka, Isao; Fujiwara, Yoshie; Hitomi, Kenichi; Cheng, Quen J.; Fuss, Jill O.; Shin, David S.; Masutani, Chikahide; Tainer, John A.; Hanaoka, Fumio; Iwai, Shigenori
Abstract : Human DNA polymeraseη (HsPolη ) plays an important role in translesion synthesis (TLS), which allows for replication past DNA damage such as UV-induced cis-syn cyclobutane pyrimidine dimers (CPDs). Here, we characterized ApPolη from the thermophilic worm Alvinella pompejana, which inhabits deep-sea hydrothermal vent chimneys. ApPolη shares sequence homology with HsPolη and contains domains for binding ubiquitin and proliferating cell nuclear antigen. Sun-induced UV does not penetrate Alvinella's environment; however, this novel DNA polymerase catalyzed efficient and accurate TLS past CPD, as well as 7, 8-dihydro-8-oxoguanine and isomers of thymine glycol induced by reactive oxygen species. In addition, we found that ApPolη is more thermostable than HsPolη, as expected from its habitat temperature. Moreover, the activity of this enzyme was retained in the presence of a higher concentration of organic solvents. Therefore, ApPolη provides a robust, human-like Polη that is more active after exposure to high temperatures and organic solvents.